'Don't make it a doctrine': Material religion, transcendence, critique. (March 2016) - Reinhardt, Bruno
Once a matter of beliefs, symbols, values and worldviews, religion has progressively appeared in recent anthropological works as material religion, a highly concrete phenomenon based on affects, senses, substances, places, artifacts, and technologies. But what happened to transcendence, the dimension of religious worldmaking that remains beyond – hidden, untouched, unseen, unheard or unfulfilled? Is it necessarily the 'other' of material religion, a residual category that carries no ethnographic value? Retaining an emic concern with authority and a reflexive awareness about processes of boundary-making, in this article I approach material religion as a field of problematization inhabited by anthropologists and religious subjects alike. I examine some of the protocols whereby Pentecostal Christians in Ghana engage critically with the problem of materiality in their own religion, and argue that this operation lends ethnographic access to the role of transcendence in material religion's everyday.